The Effect Of Easy Perception And Security Perception On The Intention Of Using Shopeepay Through Attitude As Intervening Variables In Madiun - Heny Sidanti; Dian Citaningtyas Ari Kadi; Hari Purwanto; Wahyu Sri Lestari (International Journal of Science, Technology & Management, 2022)
The purpose of this research was to determine the effect of perceived ease of use and perceived safety on Intention to Use through Attitude as an Intervening Variable for ShopeePay Users in Madiun. This research is a quantitative study using sampling techniques using nonprobability sampling with purposive sampling technique. Respondents of this study were 150 people. Data analysis used classical assumption test, hypothesis test, path analysis, and Sobel test mediation. Based on the results of the test (t), obtained the results of the perception of ease of perception and perceptions of security affect attitudes, perceptions of perceived ease of security affect intention to use with a significant value less than the alpha value of 0.05. The path analysis test obtained the results of the indirect sub-structural effect 1 Ease of perception on the intention to use through attitude as an intervening variable obtained the result that the direct effect was greater than the indirect effect. Results The indirect effect of perceptions of security on the intention to use through attitude as an intervening variable shows that the direct effect is smaller than the indirect effect. The results of the Sobel test mediation test show that the results of the perception of Security on Intention to Use through Attitude as an Intervening Variable can mediate attitudes.